Environmentally Adjusted Multifactor Productivity Methodology and Empirical results for OECD and G20 countries - Cárdenas Rodríguez, Miguel (OECD Green Growth Papers, 2016)
This paper further refines the OECD framework for measuring the environmentally adjusted multifactor productivity growth that seeks to incorporate environmental services in productivity analysis. Compared to standard productivity measurement, this framework allows accounting also for the use of natural capital (currently including 14 types of fossil fuels and minerals) and the emission of pollutants as negative by-products (currently including 8 types of greenhouse gases and air pollutants). An updated series of the indicator is presented, with a geographic coverage extended to all OECD and G20 countries for the 1990-2013 time period. The indicators presented here allow the sources of economic growth to be better identified, and growth prospects in the long run to be better assessed